FZL, a dynamin-like protein localized to curved grana edges, is required for efficient photosynthetic electron transfer in Arabidopsis - Ogawa, Yu; Iwano, Megumi; Shikanai, Toshiharu; Sakamoto, Wataru (Frontiers in Plant Science, 2023)
Photosynthetic electron transfer and its regulation processes take place on thylakoid membranes, and the thylakoid of vascular plants exhibits particularly intricate structure consisting of stacked grana and flat stroma lamellae. It is known that several membrane remodeling proteins contribute to maintain the thylakoid structure, and one putative example is FUZZY ONION LIKE (FZL). In this study, we re-evaluated the controversial function of FZL in thylakoid membrane remodeling and in photosynthesis. We investigated the sub-membrane localization of FZL and found that it is enriched on curved grana edges of thylakoid membranes, consistent with the previously proposed model that FZL mediates fusion of grana and stroma lamellae at the interfaces. The mature fzl thylakoid morphology characterized with the staggered and less connected grana seems to agree with this model as well. In the photosynthetic analysis, the fzl knockout mutants in Arabidopsis displayed reduced electron flow, likely resulting in higher oxidative levels of Photosystem I (PSI) and smaller proton motive force (pmf). However, nonphotochemical quenching (NPQ) of chlorophyll fluorescence was excessively enhanced considering the pmf levels in fzl, and we found that introducing kea3-1 mutation, lowering pH in thylakoid lumen, synergistically reinforced the photosynthetic disorder in the fzl mutant background. We also showed that state transitions normally occurred in fzl, and that they were not involved in the photosynthetic disorders in fzl. We discuss the possible mechanisms by which the altered thylakoid morphology in fzl leads to the photosynthetic modifications.